INTERPROFESSIONAL EDUCATION AS A TOOL FOR TEACHING-SERVICE INTEGRATION AND TRANSFORMATION: EXPERIENCE REPORT ON THE STUDY OF ENVIRONMENTAL DETERMINANTS AND RESPIRATORY HEALTH DISORDERS - Moro, Giullia Fernanda Borges; Chiozini, Laura Valério; Torquato, Letícia Garcia Henriques; de Lima, Maria Clara Gonçalves; Simão, Rebeca Lopes; Cotrim, Thiago Augusto; da Silva Junior, Chaudes Ferreira; Colares, Philippe; Telini, Wagner Moneda (Seven Editora, 2026)
This experience report analyzes Interprofessional Education as a central strategy within the Curricular Unit of Teaching-Service-Community Integration Practices at the Centro Universitário de Votuporanga, focusing on the study of environmental determinants and their impacts on respiratory health within the territory during the year 2024. Air pollution, intensified by an extreme rate of wildfires in the Midwest region and the transport of smoke to Votuporanga, served as the setting for a Project-Based Learning methodology that integrated students and professors from Medicine, Nursing, and Environmental Engineering. The main objective was to investigate the correlation between particulate matter levels (PM10 and PM2.5) and the volume of clinical visits at Emergency Care Units (UPA), training future professionals to identify the impact of climate conditions on acute illness and to provide support for local public management. The methodology consisted of a retrospective and quantitative study that cross-referenced ICD-10 diagnoses, such as acute upper respiratory infections (J00) and cough (R05), with data from CETESB’s automatic monitoring network. The results revealed a drastic deterioration in air quality, with PM10 increasing from 17 µg/m³ in January to a peak of 100 µg/m³ in September, accompanied by PM2.5, which reached 47.5 µg/m³ during the same period. Clinically, it was observed that, contrary to the historical pattern in which respiratory diseases decline after winter (May to July), in 2024 the incidence of cases remained high until October, coinciding with the end of the wildfire season. Age-group analysis confirmed the vulnerability of the elderly population, especially individuals over 70 and 90 years old, whose peaks in healthcare visits closely followed the atmospheric pollution curve. It was concluded that interprofessional practice clearly demonstrated the impact of environmental determinants on public health, transcending academic boundaries by providing real indicators that support healthcare actions and future public policies aimed at mitigating the effects of wildfires on population health.